PERAN NEGARA MELALUI PERUSAHAAN BUMN DALAM KASUS PENGAMBILALIHAN LAHAN DI KULON PROGO, YOGYAKARTA - Muhammad Umar Khalid (2023)
This study aims to discuss the dynamics of agrarian conflict issues in the construction of YIA Airport using the concepts of accumulation by disposition and agrarian conflict. The method used is qualitative with a case study approach using primary data sources, namely semi-structured interviews and secondary data, namely literature studies using journals, documents and articles. This study uses four stages of data analysis according to Creswell, namely organizing data, grouping coding, describing coding and interpreting data. The end result of this research is that the state becomes the main actor in land acquisition by way of accumulation through confiscation for the development of YIA Airport through overlapping policy making in order to carry out the process of land acquisition for airport development. PT Angkasa Pura I, as the executor of the airport development, acts as the owner of capital for the land acquisition process, so that helpless people are evicted from their land where they have lived for decades.